57.3k views
19 votes
Please explain this!!

*show every step of you’re work of how you solved it and then, the answers* !!

Please explain this!! *show every step of you’re work of how you solved it and then-example-1
User MrXQ
by
5.0k points

1 Answer

11 votes

Answer:

Explanation:

use Y- Y1 = m ( X - X1 )

3.

y1 = 2

x1= -4

m= 3

Y- Y1 = m ( X - X1 )

y - 2 = 3 (x + 4)

y-2= 3x + 12

y = 3x + 14

4.

y1= -1

x1= 6

m = -1

Y- Y1 = m ( X - X1 )

y + 1 = -1 (x - 6)

y + 1 = -x + 6

y = 5 - x

User Shivam Jha
by
4.9k points